Biogenesis of Hydrocarbons 2019
DOI: 10.1007/978-3-319-53114-4_21-1
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiology of Acetoclastic Methanogens

Abstract: Acetate is the most important precursor for methane in the degradation of organic matter. Only two genera of methanogenic archaea, Methanosarcina and Methanothrix (former Methanosaeta), are able to grow with acetate as sole energy and carbon source. Phylogenetically, Methanosarcina and Methanothrix both belong to the Methanosarcinales. These two genera show besides morphological differences, interesting differences in physiology. Methanosarcina is a generalist that can grow on a variety of substrates, while Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
0
10
0
1
Order By: Relevance
“…However, it has also been found that Methanothrix species can reduce CO 2 to methane by accepting electrons from exoelectrogenic bacteria via direct interspecies electron transfer (DIET) (4,19), and this is likely to further increase their contribution to methane production in anoxic environments. Although Methanothrix species are predominant members of many methanogenic communities, little is known about their physiology (1,(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has also been found that Methanothrix species can reduce CO 2 to methane by accepting electrons from exoelectrogenic bacteria via direct interspecies electron transfer (DIET) (4,19), and this is likely to further increase their contribution to methane production in anoxic environments. Although Methanothrix species are predominant members of many methanogenic communities, little is known about their physiology (1,(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…6), with the only exception of species assigned to Methanothrix genus, which increased their relative abundance from 0.2% in control up to 0.57% in nZVI reactors. Members of this genus are recognized as specialist methanogenic bacteria that only use acetate for their growth (Stams et al, 2019), a substrate for which they have greater affinity than other acetoclastic species (Smith and Ingram-Smith, 2007). This greater affinity could explain its marked rise, as it has been suggested by other studies (Röske et al, 2014), since it would be reasonable to expect that acetate concentration in nZVI reactors is lower because of the reduction in the relative abundances of acetate-producer bacteria, such as Sedimentibacter, or Syntrophomonas (Breitenstein et al, 2002;Kong et al, 2018).…”
Section: Effect Of Nzvi On Microbial Communitymentioning
confidence: 92%
“…Regarding diversity analyses, the biom file from QIIME2 was imported and analyzed through phyloseq-modified workflow (McMurdie and Holmes, 2013). Alpha diversity in each sample was calculated based on the number of observed ASVs using Shannon diversity index after rarefying, normalized with 976 sequences per samples (Shannon, 1948;Simpson, 1949). Taxon relative abundance bar charts were generated using custom R scripts and ggplot2 (v3.3.2).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Acetate is formed from decomposition of organic matter (OM) and is in the main CH4 precursor. The fate of acetate in a methanogenic environment is largely dependent on the physicochemical conditions, such as temperature, pH and salinity for example (Stams et al, 2019).…”
Section: Introductionmentioning
confidence: 99%